Pueraria tuberosa DC Extract Improves Androgenesis and Sexual Behavior via FSH LH Cascade. (30th December 2013) - Chauhan, Nagendra Singh; Sharma, Vikas; Thakur, Mayank; Christine Helena Frankland Sawaya, Alexandra; Dixit, V. K.
Abstract : The aim of this study was to investigate the effects of ethanolic extract of Pueraria tuberosa (PT) on sexual behaviour and androgenic activity. Male albino rats were divided into four groups of six animals each: control group 1 (2% acacia solution), PT-treated group 2 (50 mg/Kg), PT-treated group 3 (100 mg/Kg), and PT-treated group 4 (150 mg/Kg). Sexual behavior of male rats in the presence of a female rat was recorded. The treated groups were evaluated for sexual parameters. The extract was characterized using LC-MS. The effect of treatment on anabolic and weight of secondary sexual organs was determined. The histological changes in section of testis and epididymis after treatment were observed. Sperm count in epididymis and fructose content in seminal vesicles were also measured. Levels of hormones like FSH, LH, and T were determined. A dose-dependent increase in sexual behaviors was evidenced in the animals of extract treated groups. Increase in testis weight was recorded in PT. At the highest dose PT also affects the hormones level. The four compounds namely puerarin, daidzein, biochanin-A and formononetin were identified in ethanolic extract using LC-MS. It concluded that PT extract possesses androgenic effect and it significantly increased the sexual behaviour and hormones level.